Health Student's Anger Management Through Ego State Counseling - Hayinah, Rahayu; M, Sukmawati; Y, Sofiyah (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
This study aims to assess the effectiveness of ego state counselling in reducing anger in the high category of health students at the University of 'Aisyiyah Bandung. Anger that is appropriately expressed will make a person acceptable to the environment, help solve problems and support the individual in achieving life goals. This is a single subject study with an AB design. The research sample is thirty people, with the high anger category and the dominant and instrumental reactive anger expression type. The data is processed using visual analysis. This technique looks at trends and statistical analysis using two standard deviations and Percentage overlapping Non-Data (PND) guidelines to test the effectiveness of the intervention. Based on the research data above, it can be concluded that the use of ego state counselling effectively reduces the anger of health students. The research conducted is expected to be a study in nursing psychology courses, published widely for health institutions and essential considerations for further research with anger and ego state counselling.